Bank Bailouts : Moral Hazard vs. Value Effect - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper, 1999)
This paper shows that a central bank, by announcing and committing ex-ante to a bailout policy that is contingent on the realization of certain states of nature (for example on the occurrence of an adverse macroeconomic shock), creates a risk-reducing 'value effect' that more than outweighs the moral hazard component of such a policy.